REPRESENTASI MASKULINITAS DALAM IKLAN GARNIER MEN VERSI JOE TASLIM DAN CHICO JERIKO - Herninda Cintia Kemala Sari (sarasvati, 2020)
Television advertising is not only the most reliable medium for selling products, but also in shaping an image. Such as advertisements for facial care products for men which often highlight masculine images, where masculine is a gender concept that is pinned to men by a culture. This study aims to explore the meaning of denotation, connotation, and myth contained in the Garnier Men advertisement by Joe Taslim and Chico Jeriko. Using Roland Barthes's analysis related to signified, significant, denotative, connotative, and myth. The results showed a male masculine image, a combination of urban, metropolis, and metrosexual male images represented by denotations of races, martial arts and other urban metropolis men's activities. In connotation, showing a representation of the dominant male type in life. These signs point to the social relations of the community towards a man. This research is expected to be able to add and provide knowledge and be a reference for the public's perspective in interpreting television advertisements for men's facial cleansers.